The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/ejoc.201101766
|View full text |Cite
|
Sign up to set email alerts
|

Organocuprate‐Initiated Domino Michael–Intramolecular Aldol Reaction – Application to the Formation of Ring B of the Aglycon of Landomycins

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Removal of the benzyl group and subsequent PCC oxidation furnished the ketone 24 , which was efficiently converted into 16 . The aryltriflate 25 was derived from 2,6‐dimethoxy‐4‐methylbenzaldehyde in two steps and then transformed into the pinacol boronate 17 by Miyaura's protocol involving palladium‐catalyzed borylation with bis(pinacolato)diboron.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Removal of the benzyl group and subsequent PCC oxidation furnished the ketone 24 , which was efficiently converted into 16 . The aryltriflate 25 was derived from 2,6‐dimethoxy‐4‐methylbenzaldehyde in two steps and then transformed into the pinacol boronate 17 by Miyaura's protocol involving palladium‐catalyzed borylation with bis(pinacolato)diboron.…”
Section: Figurementioning
confidence: 99%
“…[17] Extensive screening of reaction conditions using various Lewis and Brønsted acids showed that the reaction could be promoted using ac atalytic amount (10 mol %) of trifluoromethanesulfonic acid, thus providing the aldehyde 21,having aq uaternary carbon atom (C9), as as ingle diastereomer. Adding 1,2-bis(trimethylsiloxy)ethane to the reaction mixture directly protected the aldehyde group as ad ioxolane, thus affording 22 in 79 %yield over two steps.Removal of the benzyl group and subsequent PCC oxidation furnished the ketone 24,w hich was efficiently converted into 16.T he aryltriflate 25 was derived from 2,6-dimethoxy-4-methylbenzaldehyde in two steps [19] and then transformed into the pinacol boronate 17 by Miyauras protocol [18] involving palladium-catalyzed borylation with bis(pinacolato)diboron.…”
mentioning
confidence: 99%
“…The spectroscopic data were in accordance with the reported values. 18 IR ν max (film)/cm −1 2844, 1662, 1571, 1467, 1238, 813; 1 H NMR (CDCl 3 , 400 MHz) δ 10.44 (1H, s, CHO), 6.37 (2H, s, H-3), 3.87 (6H, s, OMe) and 2.36 (3H, s, CH 3 ); 13 6-Hydroxy-2-methoxy-4-methylbenzaldehyde (11). Anhydrous AlCl 3 (7.80 g, 58.50 mmol) was added portionwise over 5 min to a stirred solution of aldehyde 10 (8.78 g, 48.73 mmol) in dry CH 2 Cl 2 (95 mL) under nitrogen.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Several efforts to achieve the desired transformation of β,β-disubstituted α,β-unsaturated electron withdrawing systems have been realised to be unsuccessful or not widely applicable. 16 The primary reason could be the incompatible nucleophilicity of the Lewis bases and the steric encumbrance of the β,β-disubstituted activated olefins.…”
Section: Phosphine-mediated Transformations Of Activated Alkenesmentioning
confidence: 99%